The Future of Performance Budgeting in Poland - Zawadzka-Pąk, Urszula Kinga (Studia Oeconomica Posnaniensia, 2013)
The key terms of performance budgeting have not yet been yet clearly defined in Polish practice, there is even a kind of definitional chaos. To systematise, at least in part, the terminology in this area it seems necessary to distinguish between a performance budget (the budget as a legal institution); a task-oriented budget (the budget in economic terms); and the system of performance planning in the sector of public finances. The performance budget is one of the main instruments of the New Public Management that is used to increase the efficiency (ratio of expenditure for public services performed) and the effectiveness (the quality) of the functioning of the public sector. This allows the obtaining of relevant information about the results achieved by public administrations and permits more transparent (understandable) budgetary information at both central and local level. However, if we want to use the performance budget as a practical tool for the rationalization of public expenditure it is necessary to conduct a comprehensive analysis of the functioning of the state, in order to identify areas where it is necessary to make changes in the law or increase the enforceability of existing laws.